Start-up Financing: How to Attract the “Right” Investors - Philippi, Stephan Albert Maria; Justus Liebig University Giessen (My University, 2021)
This dissertation draws on the logic of start-up financing as a two-sided matching model and aims at shedding further light on start-up financing by analyzing both sides of this two-sided matching model. On the one hand, start-ups are able to select their investors. In this regard, this dissertation provides insights into the effects of different types of equity investors and start-ups' survival chances. On the other hand, equity investors can select their investees. In this regard, I reveal how start-ups can attract venture capital investments and increase their fundraising success through an Initial Coin Offering. Overall, this dissertation provides clearer guidance for start-ups in terms of which specific types of investors to pursue and the means of attracting them. This knowledge can help start-ups to survive and become more successful in the long term, which is beneficial for the society.
Keywords: Startupfinanzierung; Venture Capital; Business Angels; Corporate Venture Capital; Initial Coin Offerings; ddc:650